Performance based Remuneration For Civil Sevants - BEHRENS, CHRISTOPH; PARAMITHA, PRADNYA (Universitas Muhammadiyah Yogyakarta, 2011)
Within the ongoing discussion about the Governance system in Indonesia and a reform of its PublicAdministration according to principles of Good Governance, a new remuneration system for civilservants is regarded a strategic key issue. The article outlines dimensions of the issue and gives aninsight on discourse and current reform approaches. An outlook on necessary steps ahead stresses, thatAdministrative Reform is not a topic for the